69.3k views
3 votes
1. Simplify -7 + {12 - 3[50 - 4(2+3)] }

2. Simplify 1/3 + 6 (2/3 - 1/6)^2

Thank youuu!!

1 Answer

5 votes

1. Simplify
-7 + (12 - 3[50 - 4(2+3)]) this expression step by step:


  • 2+3=5;

  • 4\cdot (2+3)=4\cdot 5=20;

  • 50-4\cdot (2+3)=50-20=30;

  • 3\cdot [50-4(2+3)]=3\cdot 30=90;

  • 12-3\cdot[50-4(2+3)]=12-90=-78;

  • -7 + (12 - 3[50 - 4(2+3)])=-7+(-78)=-7-78=-85.

2. Simplify the expression
(1)/(3) + 6\left((2)/(3) - (1)/(6)\right)^2 in the same way:


  • (2)/(3)-(1)/(6)=(2\cdot 2-1)/(6)=(3)/(6)=(1)/(2)

  • \left((2)/(3) - (1)/(6)\right)^2=\left((1)/(2) \right)^2=(1)/(4)

  • (1)/(3) + 6\left((2)/(3) - (1)/(6)\right)^2=(1)/(3) + 6\cdot (1)/(4)=(1)/(3)+(3)/(2)=(1\cdot 2+3\cdot 3)/(6)=(11)/(6)
User John Trenwith
by
5.4k points